The Influence of Leadership and Discipline on Work Involvement and Its Impact on the Performance of State Elementary School Teachers - Suwarni, Suwarni; Basrowi, Basrowi; Khaeruman, Khaeruman (Jurnal Lingua Idea, 2025)
This research aims to identify factors influencing teacher performance with work involvement as an intervening variable for state elementary school teachers in Cipocok Jaya District, Serang City. This research uses quantitative methods with a correlational approach. The research was conducted at a public elementary school in Cipocok District, Serang City. The research time is June to. August 2024. The sampling technique used was proportional random sampling with a sample size of 97 people. Data analysis uses the Structural Equation Modelling (SEM) and Smart PLS approaches. The findings reveal that transformational leadership, discipline, and work engagement positively influence teacher performance. Work involvement has a pseudo-mediation effect between Leadership and Teacher Performance. Leadership can influence teacher performance directly or indirectly by mediating work involvement management.